Employability, Poverty and the Spheres of Sociability – Evidence from the British Household Panel Survey. (1st September 2014) - Canduela, Jesus; Lindsay, Colin; Raeside, Robert; Graham, Helen
Abstract Policymakers in the UK and beyond have sought to promote interventions to encourage social capital‐building among disadvantaged groups. One specific concern is that those with limited access to social capital/social network relationships will be at greater risk of experiencing both unemployment and poverty. By analyzing longitudinal data from the British Household Panel Survey (BHPS), we seek to identify significant relationships between poverty and the likelihood of entering employment, and different measures of 'sociability' and social isolation. Crucially, we discuss if and how measures of sociability/social isolation are associated with jobseekers' varying chances of exiting and re‐entering work and how this varies with their experience of poverty. These issues are important because if sociability impacts on the likelihood of entering employment from a state of worklessness, then policymakers need to understand how cycles of social and labour market exclusion are associated with the rates of entering employment in order to develop effective interventions to improve jobseekers' employability and combat poverty. Following an analysis of BHPS data, we identify lessons for policy for combating long‐term unemployment and promoting social inclusion.